2021
DOI: 10.1186/s13023-021-01809-1
|View full text |Cite
|
Sign up to set email alerts
|

A multi-stakeholder multicriteria decision analysis for the reimbursement of orphan drugs (FinMHU-MCDA study)

Abstract: Background Patient access to orphan medicinal products (OMPs) is limited and varies between countries, reimbursement decisions on OMPs are complex, and there is a need for more transparent processes to know which criteria should be considered to inform these decisions. This study aimed to determine the most relevant criteria for the reimbursement of OMPs in Spain, from a multi-stakeholder perspective, and using multicriteria decision analysis (MCDA). Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 33 publications
(16 reference statements)
0
11
0
Order By: Relevance
“…MCDA has been used in a diverse range of health care decisions and levels [18,32]. At the macro level, it has been mostly used by HTA bodies to rank and set priorities among therapeutic alternatives and inform reimbursement decisions [20][21][22][23]25,33], and it has also has been proposed for the benefit-risk assessment to support marketing…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MCDA has been used in a diverse range of health care decisions and levels [18,32]. At the macro level, it has been mostly used by HTA bodies to rank and set priorities among therapeutic alternatives and inform reimbursement decisions [20][21][22][23]25,33], and it has also has been proposed for the benefit-risk assessment to support marketing…”
Section: Discussionmentioning
confidence: 99%
“…MCDA has been used in a diverse range of health care decisions and levels [ 18 , 32 ]. At the macro level, it has been mostly used by HTA bodies to rank and set priorities among therapeutic alternatives and inform reimbursement decisions [ 20 , 21 , 22 , 23 , 25 , 33 ], and it has also has been proposed for the benefit–risk assessment to support marketing authorisation [ 34 ]. At lower decision levels, MCDA has been used to inform hospital decision making to incorporate medicines into the hospital formulary [ 24 ] and also to support shared decision making involving the patient’s voice [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that using health technology assessment (HTA) approaches typically results in rare disease drugs not being cost-effective [ 38 , 39 , 40 ]. The multi-criteria decision analysis (MCDA) framework as a tool for assessing the value of rare disease drugs has improved the technical and ethical quality of decisions regarding prioritization, coverage, and reimbursement of rare diseases [ 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite their low prevalence, they are life-threatening or chronically debilitating conditions with a high burden and very often limited level of awareness [ 1 , 4 ]. RDs have a high impact on patients, their families, healthcare systems and even society in general, and are characterized by pain, disability, significant organ damage, and high mortality rates [ 5 ]. Although their prevalence is low, RDs are numerous and heterogeneous [ 6 ].…”
Section: Introductionmentioning
confidence: 99%